Design Of Supercapacitor Energy Storage System - Sekhar, Dr.P.Chandra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Reactive power will be essential to deliver the active power with the help of transmission lines to preserve the voltage. If the reactive power is not efficient, the voltage fallsthan the power required to load through the lines is not possible.So in order to deliver this required power in an effective way, we use technologies such asSVCs (Static voltage compensation), FACTS i.e Flexible AC transmission system, STATCOMs(Static VAR compensators),etc for the maintenance of high power factor voltage stability as well as to minimize the transmission losses. STATCOMs are commonlyhelps to increase thestability of power system. power system, can exchange the reactive power, then which will limited the exchange of gereal power, so that the energy storage devices are may not include. The STATCOMs associate with the energy storage device like batteries which released to increase real power exhange, this kind of batterieshadbarrier in their max deliverable power dueto the chemical process slowneed to release its energy. In recent days, the usage of SCESS as energy storage to STATCOM. We have less energy storage for Super capacitors. Still they have capability of the high level power exchanging than batteries. The Document represents controland supercapacitor energy storage system analysis i.e SCESS form STATCOM. The controller of current mode wasmainly used for regulating SCESS. The Simulation model of the SCESS is developed and the same simulation results should be presented for the proposed SCESS system.